The MMP3 gene in musculoskeletal soft tissue injury risk profiling: A study in two independent sample groups. Issue 7 (3rd April 2017) - Gibbon, A.; Hobbs, H.; van der Merwe, W.; Raleigh, S. M.; Cook, J.; Handley, C. J.; Posthumus, M.; Collins, M.; September, A. V.
ABSTRACT: Matrix metalloproteinase-3 (MMP3) is a mediator of matrix remodelling and a proposed susceptibility locus in the genetic profile of musculoskeletal soft tissue injuries. Therefore, this study aimed to validate the MMP3 gene as a risk marker for these injuries by conducting a case control genetic association study in two independent samples groups. Three previously investigated MMP3 variants (rs679620, rs591058 and rs650108) in addition to the functional promoter variant (rs3025058) were genotyped in 195 Australian control participants and 79 Australian individuals with chronic Achilles tendinopathy. Similarly, 234 South African individuals with acute anterior cruciate ligament ruptures and 232 matched control participants were also analysed. Based on high linkage with the previously associated MMP3 variant rs679620, rs3025058 was inferred and found to be associated with increased risk for Achilles tendinopathy within the South African group ( P  = 0.012; OR: 2.88; 95% CI: 1.4 to 6.1). Lastly, the 6A-G-C-G haplotype, constructed from the investigated variants, was significantly associated with reduced risk for Achilles tendinopathy (29% CON vs. 20% TEN, P  = 0.037) in the Australian group. In conclusion, a signal surrounding MMP3 is apparent with respect to Achilles tendinopathy. However, whether the investigated variants are contributing to injury susceptibility or whether they are merely linked to the risk conferring variants mapping elsewhere within the MMP gene cluster on chromosome 11, still requires refining.